EFFECT OF MOISTURE REGIMES AND INOCULATION ON GROWTH AND YIELD OF BAMBARA GROUNDNUT IN NORTHERN GUINEA SAVANNAH OF NIGERIA - Ladan, Kabir Muhammad; Kura, Habu N.; Sani, Bashir M. (FUDMA JOURNAL OF SCIENCES, 2025)
The experiment was conducted to evaluate the effect of Moisture regimes and inoculation on growth and yield of Bambara groundnut in dry season of 2021/2022 at irrigation farm of College of Agriculture and Animal Science, Mando Kaduna and Institute for Agricultural Research IAR, A.B.U., Samaru-Zaria, both located in the Northern Guinea Savannah Ecological Zone of Nigeria respectively. Treatments consisted of four levels of moisture regimes (25%, 50%, 75%, and 100%) and two levels of inoculation; no inoculation and inoculation. Treatment were factorially combined in a randomized complete block design (RCBD) and replicated three times. Data on growth parameter were collected on number of leaves, number of branches, net assimilation rate, days to 50% flowering and kernel yield kg/ha were collected. Results showed that 100% moisture regime significantly resulted in highest growth indices like number of leaves, number of branches, net assimilation rate, days to 50% flowering and kernel yield kg/ha of Bambara groundnut over other regimes evaluated. While inoculation of Bambara groundnut significantly resulted in higher performance in both growth and yield parameters evaluated over non-inoculated Bambara groundnut plants. From the results obtained, the combination of 100% moisture regimes produced better performance on growth and yield of inoculated Bambara groundnut at both locations.
Keywords: Moisture regimes; Bambara groundnut; Inoculation; Growth; Yield; Nigerian Savannah